Price transmission and market integration of fish in Oyo State (2010)
This study examined degree of market integration and price transmission between four categories (local fresh, local dried, imported iced and imported dried) of fish market in the rural and urban area of Oyo State. Secondary data were sourced on the monthly retail prices of fishes for sixty months from the Oyo State Agricultural Development Project (OYSADEP). Data were analysed using the Augmented Dickey Fuller (ADF) test, Granger-causality test and Index of Market Concentration. The result revealed that while the other three market pairs were well integrated, the rural and urban local fresh fish market were not well integrated as the pair accept the null hypothesis of no integration, prices of the local and urban fresh fish market were not tied together in the long run. Thirty-one market links rejected the null hypothesis of no granger causality; seventeen market links exhibit a uni-directional granger causality while fourteen market links exhibit a bi-directional granger causality. The urban fresh fish market occupies the leadership position in the price formation and transmission in the markets investigated. The Index of market connection (IMC) indicates that the markets exhibit low short run market integration. It is therefore recommended that there is need for a policy to ensure efficient marketing of fresh fish in the urban and rural area of the State.